Degenerative Disk Disease at Lumbosacral Junction: Plain Film Findings and Related MRI Abnormalities - Suphaneewan Jaovisidha (2018)
Due to a wide range of normal disk space heights at lumbosacral (LS) junction, we conducted this study to evaluate how to diagnose degenerative disk disease (DDD) of LS junction and how much information we can obtain from plain radiography regarding this condition. We retrospectively reviewed lateral LS spine films and magnetic resonance (MR) imaging in 100 patients presented with low back pain. Anterior disk height (ADH) and posterior disk height (PDH) were directly measured from plain radiographs. Signs of DDD were recorded from both plain radiographs and MR imaging. We found that ADH < 11.3 mm or PDH < 5.5 mm indicate DDD at LS junction with 95 per cent confidence interval. When spondylolisthesis presented, disks were all degenerated. Endplate sclerosis had significant relative risk (p < 0.05) for lateral neural canal stenosis and disk herniation. No radiographic finding showed significant relative risk for nerve root compression.